Enhancement of the bearing strength of pinned-joint composite materials - Aktas, Alaattin; Isguzar, Tugce; Dogu, Mustafa; Arslan, Alihan (SAGE PUBLICATIONS LTD, 2025)
In this study, a different approach is used to enhance the bearing strength in continuous carbon fiber epoxy composite materials. In order to enhance the bearing strength, metal washers are inserted between laminae of composite material in the region of the pin. Two types of washer, one is stainless steel and the other is aluminum, are used in the preparation of specimens to carry out the bearing strength tests. In addition, three metal washer inserting configurations, as embedding one, two, or three washers in between carbon fiber layers, are tested in each group of specimens. The results show that the first bearing strength values obtained from the specimens with stainless steel washers increase considerably with respect to specimens with aluminum washers and the specimens without washers. The maximum strength of the specimens reinforced with one, two, and three stainless steel washers is approximately 185%, 405%, and 390% higher than the reference specimen, respectively. It is also observed that the maximum strength of the specimens reinforced with one, two, and three aluminum washers is 265%, 285%, and 320% higher than the reference specimen, respectively.
Keywords: Bearing strength; failure modes; metal reinforced; pin joint; STACKING-SEQUENCE; FAILURE ANALYSIS; EPOXY; PARAMETERS; Materials Science; Polymer Science